Nihilent technologies: recommending change at the banking : recommending change at the Banking Association South Africa. (A) - Metton, Eulalie (SAGE knowledge. Cases., 2016)
In September 2008 Ravi Teja, associate vice president and head of enterprise transformation at the global consulting company, Nihilent, reviewed progress on the Banking Association South Africa project. Nihilent's analysis of the situation clearly showed that there was a need to restructure the organisation and that an effective performance management system should be put in place to enable it to achieve its objectives. The challenge was how to do this without unnecessarily alienating Banking Association employees, and this was one of the key points on the agenda.